2020
DOI: 10.1007/s00431-020-03624-5
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal function after induction therapy for acute lymphoblastic leukemia in children short: adrenal function in ALL

Abstract: Prednisolone used in the induction phase of the treatment of acute lymphoblastic leukemia (ALL) may suppress hypothalamic-pituitary-adrenal axis and require hydrocortisone substitution. In this retrospective analysis, we reviewed altogether 371 ACTH stimulation tests of 352 children after a uniform NOPHO (Nordic Society of Pediatric Hematology and Oncology) ALL induction. Both low-and standard-dose ACTH tests were used. Full recovery of adrenal function was defined by both normal basal and stimulated cortisol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 16 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…Research has shown that children receiving induction therapy for ALL during which high dose GC are used, are at high risk of biochemical AS after the end of induction. [2][3][4] In a Cochrane review, 11 of 10 studies including 298 pediatric patients with ALL, almost all patients were found to have biochemical evidence of AS within days of finishing GC therapy. Most children recovered from adrenal insufficiency within 7 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research has shown that children receiving induction therapy for ALL during which high dose GC are used, are at high risk of biochemical AS after the end of induction. [2][3][4] In a Cochrane review, 11 of 10 studies including 298 pediatric patients with ALL, almost all patients were found to have biochemical evidence of AS within days of finishing GC therapy. Most children recovered from adrenal insufficiency within 7 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Although most patients in that review had AS immediately after GC exposure, some had prolonged AS. In 2 studies where post-induction hydrocortisone replacement was routine, 2,4 patients seemed to have a more prolonged recovery. Extrapolating from these previous studies, our finding of abnormal, although borderline, LDST may represent resolving AS secondary to elapsed time since last GC exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concurrent use of fluconazole during dexamethasone therapy was associated with prolonged HPA recovery ( 34 ). This is due to the inhibition of CYP3A4 by fluconazole, which results in decreased metabolism of corticosteroid and increased corticosteroid exposure to the HPA axis ( 35 ). Itraconazole is an even more potent inhibitor of CYP3A4, and secondary adrenal insufficiency was reported to occur in a patient on inhaled fluticasone and itraconazole ( 31 ).…”
Section: Discussionmentioning
confidence: 99%